In the inner sanctum : behind the scenes at big fights - Hauser, Thomas (The University of Arkansas Press, 2022)
"In the Inner Sanctum, Thomas Hauser's latest essay collection, explores the fight night in boxing. Hauser chronicles the most dramatic hours in boxers' lives-the very moment when a fighter's physical well-being and financial future are on the line, when the fighter is most at risk and most alive"--